The low level of vitamin D3 among Type 1 Diabetes Mellitus (T1DM) children at Saiful Anwar General Hospital, Malang, Indonesia - Harjoedi Adji Tjahjono; Wisnu Barlianto; Dian Handayani; Handono Kalim (Pediatric Sciences Journal, 2022)
Background: The Type 1 Diabetes Melitus (T1DM) is a disease which is occurred because of autoimmune destruction in pancreas islet (insulin-producing ß cells). A Failure mechanism of immunoregulator causes inflammatory process in the islets and continue to damage the pancreatic β cell. Vitamin D deficiency may increase the risk of autoimmune diseases including type 1 diabetes mellitus. The aim of this study was to know the level of vitamin D in type 1 diabetes mellitus. Methods: An observational analytic cross-sectional design was conducted among 40 T1DM subjects and 40 healthy controls aged between 10-18-year-old. They were not having local or systemic infection, nor liver and kidney disorders. Vitamin D levels were measured by the ELISA method (ng/ ml). Subjects’ data were collected and processed by 2007 Microsoft Excel software, then analyzed with SPSS version 16.0 for Windows. Results: Most of respondents in T1DM group were female (57.5%) and 15.94±1.00 years old for average age but not statistically significant compared with control group (p>0.05). There was a significant different of the mean level of vitamin D3 in the T1DM group (10.41 + 2,20 ng/ml) compared with control group (18.41 + 1.41 ng/ml) (p<0,05). Conclusion: The level of vitamin D (25 (OH) D3) in the T1 DM group were significantly lower compared to the control group